Personality and Legal Culture - Angelo, AH (Victoria University of Wellington Law Review, 1996)
The interaction of Maori law and the European based state law of New Zealand has given rise to much discussion and political debate. The contemporary focus has been primarily on the Treaty of Waitangi and the work of the Waitangi Tribunal. Public interest has been attracted by the property aspects of Treaty claims and by their justness, but there has been less public interest in the Maori cultural aspects of claims. In particular, the cultural importance of some claims has been masked by concerns about the resource value involved. This article seeks to redirect attention to an aspect of the Maori cultural meaning involved where claims concern taonga, and it suggests further that coherence of claims settlements may in some cases be advanced by reference to the concept of personality.